2019
DOI: 10.1007/s10701-019-00248-0
|View full text |Cite
|
Sign up to set email alerts
|

Position Measurement-Induced Collapse: A Unified Quantum Description of Fraunhofer and Fresnel Diffractions

Abstract: Position measurement-induced collapse states are shown to provide a unified quantum description of diffraction of particles passing through a single slit. These states, which we here call 'quantum location states', are represented by the conventional rectangular wave function at the initial moment of position measurement. We expand this state in terms of the position eigenstates, which in turn can be represented as a linear combination of energy eigenfunctions of the problem, using the closure property. The ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…By this approach, only the Fraunhofer-type patterns were obtained on the screen, for all distances from the slit. In contrast, in [7] we postulated that the time-evolution of the collapsed state is described by the PMIC wave function. It was shown that this results in a single expression that describes the Fresnel and Fraunhofer diffraction.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…By this approach, only the Fraunhofer-type patterns were obtained on the screen, for all distances from the slit. In contrast, in [7] we postulated that the time-evolution of the collapsed state is described by the PMIC wave function. It was shown that this results in a single expression that describes the Fresnel and Fraunhofer diffraction.…”
Section: Discussionmentioning
confidence: 94%
“…In this paper we have also used the trajectory representation in quantum mechanics, which accept the existence of particle trajectories associated with the wave functions. In [7], we have used this additional postulate to obtain the single expression that gives a unified description of Fresnel and Fraunhofer diffractions. It was noted that all the three trajectory formulations make identical predictions in this case and that the success of our PMIC description supports the existence of particle trajectories.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations